Beneath a weeping sky - Zafiro, Frank (Gray Dog Press, 2009)
"River city is plagued by a serial rapist. His attacks are becoming more brutal and Detective John Tower is sure that he'll go from rape to murder if he isn't stopped soon. When a series of missteps and near misses push the rapist even further, everyone involved must face their old fears, or be destroyed by them"--P. [4] cover.